BRAF V600E mutation-specific antibody: A review - Ritterhouse, Lauren L; Barletta, Justine A (Seminars in diagnostic pathology, 2015)
The significance of BRAF mutations in neoplasia was first recognized in 2002 when mutations were discovered in a broad range of cancers. Numerous subsequent studies expanded our understanding of BRAF V600E as a critical diagnostic, prognostic, and predictive biomarker in many cancers. Additionally, the advent of small-molecule inhibitors of BRAF V600E rendered assessment of BRAF mutation status essential in tumors such as melanoma. In clinical practice, evaluation of BRAF mutation status has routinely been performed by DNA-based assays utilizing polymerase chain reaction (PCR). However, molecular testing is not available at many hospitals since it is time-consuming, expensive, and requires expertise in molecular techniques. The first BRAF V600E-specific antibody was reported in 2011 (clone VE1). A purified version of this antibody as well as a second monoclonal antibody targeted to BRAF V600E is now commercially available. In this review, clinicopathologic characteristics associated with BRAF-mutant tumors will be highlighted, and the prognostic and predictive implications of a BRAF V600E mutation will be discussed with a focus on melanoma, thyroid carcinoma and colorectal carcinoma. Additionally, we will review the correlation between immunohistochemistry and molecular results and deliberate how BRAF immunohistochemistry might be utilized in the evaluation of these tumors.